Vivência do enfermeiro no cuidado humano na Unidade de Terapia Intensiva adulto - Albuquerque, Nicelha Maria Guedes de (2007)
The purpose of the study was to understand the nurse s experience with human care in the Adult Intensive Care Unit (ICU). The objective was to describe the nurse s experience in caring for patients in the ICU and to analyze the nurse s perception of the care provided. The study is a descriptive inquiry of qualitative nature with a phenomenological approach. We interviewed eight nurses, 26 and 43 years of age, that provide care in the ICU of a private hospital in Natal/RN, during the manths of July and August of 2006. We analyzed the data acording to the method of Colaizzi. Four categories emerged from the data: The search for the maintenance of life, The technicalbureaucratic activities, The recognition of the patient s individuality, and the expression of the nurse s feelings.The analysis allowed us to describe the lived experience of the nurse s care the ICU and to comprehend the structural elements of this experience. The results showed that the nurse s experience presents itself as a process of the several actions and feelings that occur while the social relations between the patient and the nurse develop. Finally, we understand that although the study shows an experience based on a biological model of health, these nurses possess an initial idea on how to reach humanized care in its essence, needing, however, of an institutional policy that favors this practice, an educational formation that prepares her to recognize her field of work as a place of continuous learning and an understanding of the health model as an ally in the search of humanized care